KEPASTIAN HUKUM DALAM PENDEKATAN RESTORATIVE JUSTICE PADA PERKARA KEKERASAN DALAM RUMAH TANGGA - Susanna, Eva; Kamaruzzaman, Yusnaidi; Fitriliana, Fitriliana; Hasan, Salwa Hayati; Kesumawati, Kesumawati (Universitas Ubudiyah Indonesia, 2025)
This study discusses legal certainty in the process of resolving domestic violence cases using the restorative justice approach method. The results of the study indicate that legal certainty in restorative justice is not the same as legal certainty in the criminal law trial process, restorative justice does not replace criminal law. Restorative justice functions as an alternative approach to resolving cases, especially cases that are minor or complaint offenses with a focus on restoring relations between the perpetrator, victim, and community. Legal certainty in the restorative justice approach to domestic violence cases is carried out in the form of peace efforts outside the court, namely the process of mediation and dialogue between the victim and the perpetrator by involving the victim's and perpetrator's families, and if necessary can involve stakeholders in the form of religious leaders and traditional leaders, who together deliberate to find a way out of the violence while still paying attention to efforts to restore the victim, and the perpetrator is responsible for his actions by setting aside the criminal process.